2008
DOI: 10.1002/dvg.20496
|View full text |Cite
|
Sign up to set email alerts
|

De Novo DNA methylation independent establishment of maternal imprint on X chromosome in mouse oocytes

Abstract: Mouse blastocyst stage embryo stained for histone H3 lysine-27 trimethylation (red) and DNA (blue). H3K27me3 marks the inactive X chromosome. The study by Chiba et al. in this issue suggests that de novo DNA methyltransferases are dispensable for setting the imprint on the maternally-derived X chromsome in growing oocytes. See Chiba et al. in this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Our conditional knockout mice should be useful for investigating the molecular mechanisms that establish the maternal imprints in oocytes. Indeed, we have recently used these mice to explore the mechanisms of imprinting of maternal X‐chromosome and contribution of the oocyte‐derived Dnmts in the maintenance of autosomal imprints in preimplantation embryos (Chiba et al. 2008; Hirasawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our conditional knockout mice should be useful for investigating the molecular mechanisms that establish the maternal imprints in oocytes. Indeed, we have recently used these mice to explore the mechanisms of imprinting of maternal X‐chromosome and contribution of the oocyte‐derived Dnmts in the maintenance of autosomal imprints in preimplantation embryos (Chiba et al. 2008; Hirasawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in Robertsonian translocations in which zygotes with two maternal X chromosomes were generated, both remained active in the early embryo and the trophoblast (Goto and Takagi, 1998). The nature of this maternal imprint is unknown, but it was shown not to require acquisition of de novo DNA methylation (Chiba et al, 2008). In mice, the epigenetic maternal imprint could possibly activate expression of Tsix, an antisense transcript that prevents expression of Xist RNA.…”
Section: Developmental Cellmentioning
confidence: 99%
“…Previous studies using nuclear transfer approaches have suggested that genomic imprinting of Xist is established during oogenesis (Tada et al 2000;Oikawa et al 2014). However, analyses of DNA methyltransferase maternal knockout embryos revealed that oocyte DNA methylation is dispensable for Xist imprinting (Chiba et al 2008). A recent study demonstrated that overexpression of an H3K9me3 demethylase, Kdm4b, in parthenogenetic (PG) embryos partially derepresses Xist (Fukuda et al 2014), suggesting the involvement of H3K9me3 in imprinted Xist silencing.…”
mentioning
confidence: 99%